Effect of traumatic brain injury on mild behavioral impairment domains prior to all‐cause dementia diagnosis and throughout disease progression. Issue 1 (9th December 2022) - Bray, Michael J. C.; Bryant, Barry R.; Esagoff, Aaron I.; Richey, Lisa N.; Rodriguez, Carla; Krieg, Akshay; McCullough, Gardner; Tsai, Jerry; Tobolowsky, William; Jahed, Sahar; Cullum, C. Munro; LoBue, Christian; et al.
Abstract: Introduction: Traumatic brain injury (TBI) may alter dementia progression, although co‐occurring neuropsychiatric symptoms (NPS) have received less attention. Originally designed to evaluate behavioral disruption prior to dementia diagnosis, the mild behavioral impairment (MBI) construct relates NPS to underlying neural circuit disruptions, with probable relevance across the progression of neurodegenerative disease. Therefore, the MBI construct may represent a valuable tool to identify and evaluate related NPS both preceding diagnosis of all‐cause dementia throughout the progression of disease, representing an important area of inquiry regarding TBI and dementia. This investigation sought to evaluate the effect of TBI on NPS related by the MBI construct in participants progressing from normal cognitive status to all‐cause dementia. Methods: Using National Alzheimer's Coordinating Center data, individuals progressing from normal cognition to all‐cause dementia (clinician diagnosed) over 7.6 ± 3.0 years were studied to estimate prevalence of MBI domains in 124 participants with prior TBI history (57 with loss of consciousness [LOC] <5 minutes, 22 with LOC >5 min, 45 unknown severity) compared to 822 without. MBI domain prevalence was evaluated (1) prior to dementia onset (including only time points preceding time at dementia diagnosis, as per MBI's original definition) and (2) throughout dementia progression (evaluating all available time points, including both before and after dementia diagnosis). Results: More severe TBI (LOC >5 minutes) was associated with the social inappropriateness MBI domain (adjusted odds ratio = 4.034; P = 0.024) prior to dementia onset, and the abnormal perception/thought content domain looking across dementia progression (adjusted hazard ratio [HRadj ] = 3.703; P = 0.005). TBI (all severities) was associated with the decreased motivation domain looking throughout dementia progression (HRadj. = 1.546; P = 0.014). Discussion: TBI history is associated with particular MBI profiles prior to onset and throughout progression of dementia. Understanding TBI's impact on inter‐related NPS may help elucidate underlying neuropathology with implications for surveillance, detection, and treatment of behavioral concerns in aging TBI survivors. Highlights: The mild behavioral impairment (MBI) construct links related neuropsychiatric symptoms (NPS) by probable underlying neural network dysfunction. Traumatic brain injury (TBI) with loss of consciousness (LOC) > 5 minutes was associated with pre‐dementia social inappropriateness. TBI was associated with decreased motivation looking across dementia progression. TBI with LOC > 5 minutes was associated with abnormal perception/thought content. The MBI construct may be useful for examining related NPS across dementia progression.